Teknik Pembuatan Sediaan Mikroskop Elektron - Daryanto, Daryanto (Universitas Gadjah Mada, 1980)
This article describe a practical method in making preparation of animal tissues for electron microscopy. This method has been carried out on rat tissue in the Department of Anatomy, Faculty of Science, Mahidol University, Bangkok, Thailand.Problems in fixation, dehydration, infiltration, embedding, sectioning and cutting. and staining are discussed. The author emphasized the needs for doing tissue work with an electron microscope in tune with the development of histology in Indonesia.Key Words: electron microscope - practical methods in eletron microscopy - histochemistry - sectioning - fixation